Challenges of African Transformation : Exploring Through Innovation Approach - Baskaran, Angathevar; Muchie, Mammo (UPCC book collections on Project Muse., 2012)
A brief overview of the African economic picture reveals a paradox where the continent that has rich mineral resources, nearly a billion people and a land mass which includes the sizes of China, USA, India, Western Europe, Argentina together and still is larger than the sum of these regions is in an unacceptable state of being an object of aid, debt and loans despite the vast resources both known and yet to be expolored in it for the whole post-colonial period.